Genotyping and Macrolide Resistance of Mycoplasma Pneumoniae Identified in Children with Community-Acquired Pneumonia (CAP) in Medellín-Colombia (2018)
ABSTRACT: Objectives: The aim of this study was to describe the genotypes and the main characteristics of community-acquired pneumonia (CAP) caused by Mycoplasma pneumoniae in hospitalized children in Medellín and neighboring municipalities during the period 2011–2012. Methods: The M. pneumoniae genotype was determined by PCR and sequencing of the p1 and 23S Rrna genes from induced sputum samples and nasopharyngeal swabs (NPS). Samples were obtained from children with CAP who were hospitalized in 13 healthcare centers. In addition, a spatio-temporal analysis was performed to identify the potential risk areas and clustering of the cases over time. Results: A variant of type 2 was the dominant genotype in the induced sputum (96.1%) and NPS (89.3%) samples; the type 1 variant was identified in 3.9% and 10.7% of these samples, respectively. No strains with mutations in the 23S rRNA gene associated with macrolide resistance were found. The cases in Medellín were mainly concentrated in the northeastern areas and western districts. However, no temporal relationship was found among these cases. Conclusions: A variant of type 2 of M. pneumoniae prevailed among children with CAP during the study period. No strains with mutations associated with macrolide resistance were found.